Standards for conducting legal due diligence: Current developments: Standar dalam melakukan uji tuntas hukum: Perkembangan saat ini - Multazam, Mochammad Tanzil; Phahlevy, Rifqi Ridlo; Huzairin, Regita Amanah; Purnama, Melati Indah (Indonesian Journal of Law and Economics Review, 2022)
This study aims to provide an overview of current legal due diligence standards. So that it can be an answer to the various due diligence models used in previous studies. This research is a desk research, with literature sourced from the lens.org database and garuda.kemdikbud.go.id for scientific articles, and book.google.com for books. The result of this research is that legal due diligence has the same objective as legal audit, namely risk mitigation. The absence of standards for legal due diligence in general, can be filled with existing standards in legal audits, except for legal due diligence conducted by stock market legal consultants within the scope of the stock market. Because they already have special standards set by their association. The results of this research are expected to facilitate legal practice in conducting legal due diligence in the future. Highlights: Legal due diligence and legal audit share the same objective of risk mitigation. Existing standards in legal audits can be used to fill the absence of standards for legal due diligence. Stock market legal consultants have special standards set by their association for conducting legal due diligence within the scope of the stock market. Keywords: legal due diligence; legal audits; legal profession; law consultant; legal education